STRATEGI KOMUNIKASI BADAN PERMUSYAWARATAN DESA DALAM MENGHENTIKAN PESTA MALAM DI DESA SAWANG LEBAR KECAMATAN TANJUNG AGUNG PALIK KABUPATEN BENGKULU UTARA: COMMUNICATION STRATEGY OF VILLAGE CONSULTATIONAL BOARDS IN STOPPING A NIGHT PARTY IN THE VILLAGE SAWANG LEBAR TANJUNG AGUNG PALIK DISTRICT NORTH BENGKULU DISTRICT - Hafidzah; Nazar (JOISCOM (Journal of Islamic Communication), 2024)
This research examines or discusses the Communication Strategy of the Village Consultative Body in Stopping Night Parties in Sawang Lebar Village, Tanjung Agung Palik District, North Bengkulu Regency. Because of the many negative impacts that are felt, it is feared that if night parties continue to be held the impacts that occur will be worse, and it is also feared that it could become a new culture or habit, because night parties are held continuously and repeatedly, therefore many people and community leaders and religious instructors who are restless and disturbed and report to the Village Consultative Body because they feel this is part of their responsibility because it is a violation of village customs and religion. The purpose of this research was to find out what strategies were used by the Village Consultative Body so that it could stop the night party that had been going on for 8 (eight) months in Sawang Lebar village, Tanjung Agung Palik subdistrict, North Bengkulu district. The theoretical basis of communication strategy is the planning and preparation of communication stages carried out by communicators in order to convey messages and information to communicants to achieve a goal. The researcher used a descriptive qualitative methodology, which is appropriate because the data needed mainly consists of information and interviews from informants. Data for this study were collected through consultation with the village government and members of the Sawang Lebar village community. To collect the necessary information, the researcher used several techniques, including observation, interviews, and documentation. The research findings indicate that the strategy implemented by the Village Consultative Body to limit night parties involves formulating village regulations that prohibit night parties and the sale of alcoholic beverages in densely populated areas. Keywords: Communication Strategy, Night Party